Printing a static progressive orthosis for hand rehabilitation. Issue 8 (17th June 2021) - Huang, Li-Ying; Wang, Tien-Hsiang; Chang, Bao-Chi; Huang, Chia-I; Chou, Li-Wei; Wang, Shyh-Jen; Chen, Wei-Ming
Abstract : Background: Static progressive orthosis is used for the treatment of severe joint contracture after trauma and/or surgery. However, a custom-fabricated static progressive splint would be expensive and labor intensive. Especially, owing to very limited payment under the current Taiwanese National Health Insurance, the incentives to fabricate a patient-specific splint are insufficient for a therapist. To ease splint construction, we introduced three-dimensional (3D)-printed "shark fin"-shaped device works as a static progressive orthosis for the hand rehabilitation. The aim of this study was to describe and demonstrate the newly designed device. Methods: This study included a 46-year male suffered from a left distal radius fracture and underwent open reduction internal fixation and a 23-year male with the right thumb flexor pollicis longus rupture, requiring tendon repair. Both subjects used this "shark fin"-shaped device to stretch for increasing range of motion (ROM) of wrist extension and the thumb. Results: The patient receiving ulnar shortening surgery used this device to stretch for increasing ROM of wrist extension. The active ROM of wrist extension improved from 30° to 50°. The other patient with the right thumb flexor pollicis longus rupture suffered from thumb contracture; the ROMs of the metacarpophalangeal (MCP) joint and interphalangeal (IP) joint were 40°–55° and 20°–25°, respectively. After tenolysis surgery, his ROMs of the MCP and IP joints were improved to 10°–35° and 40°–65°, respectively. Following physical therapy by applying the device, his ROMs of the MCP and IP joints were further increased to 0°–40° and 25°–70°, respectively. Conclusion: Incorporating the "shark fin"-shaped orthosis into hand rehabilitation increased the ROM of wrist extension for a patient with distal radius fracture and improved the ROM of the MCP and IP joints in another patient after tenolysis surgery.